Magnetic materials : fundamentals and applications - Spaldin, Nicola A. (Nicola Ann), 1969- (Cambridge : Cambridge University Press, 2011)
'Magnetic Materials is an introduction to the basics of magnetism, magnetic materials, and their applications in modern device technologies. Retaining the concise style of the original, this edition has been thoroughly revised to address significant developments in the field, including the improved understanding of basic magnetic phenomena, new classes of materials, and changes to device paradigms. With homework problems, solutions to selected problems, and a detailed list of references, Magnetic Materials continues to be the ideal book for a one-semester course and as a self-study guide for researchers new to the field. This edition consists of new chapters on exchange-bias coupling, multiferroic and magnetoelectric materials, and magnetic insulators; substantial updates to the chapters on magnetic recording and magnetic semiconductors, incorporating the latest advances in the fields; and new example problems with worked solutions'--
Includes bibliographical references and index.
Keywords: Magnetic materials; Electronic apparatus and appliances -- Materials